Mutation of the XIST gene upregulates expression of X‐linked genes but decreases the developmental rates of cloned male porcine embryos. Issue 6 (4th May 2017) - Yang, Yang; Wu, Dan; Liu, Dewu; Shi, Junsong; Zhou, Rong; He, Xiaoyan; Quan, Jianping; Cai, Gengyuan; Zheng, Enqin; Wu, Zhenfang; Li, Zicong
Abstract : XIST is an X‐linked, non‐coding gene responsible for the cis induction of X‐chromosome inactivation (XCI). Knockout of the XIST allele on an active X chromosome abolishes erroneous XCI and enhances the in vivo development of cloned mouse embryos by more than 10‐fold. This study aimed to investigate whether a similar manipulation would improve cloning efficiency in pigs. A male, porcine kidney cell line containing an EGFP insert in exon 1 of the XIST gene, resulting in a knockout allele ( XIST‐ KO), was generated by homologous recombination using transcription activator‐like effector nucleases (TALENs). The expression of X‐linked genes in embryos cloned from the XIST ‐KO kidney cells was significantly higher than in male embryos cloned from wild‐type (WT) kidney cells, but remained lower than that of in vivo fertilization‐produced counterparts. The XIST ‐KO cloned embryos also had a significantly lower blastocyst rate and a reduced full‐term development rate compared to cloned WT embryos. These data suggested that while mutation of a XIST gene can partially rescue abnormal XCI, it cannot improve the developmental efficiency of cloned male porcine embryos—a deficiency that may be caused by incomplete rescue of abnormal XCI and/or by long‐term drug selection of the XIST ‐KO nuclear donor cells, which might adversely affect the developmental efficiency of embryos created from them.